Analyzing Sector‐Specific CSR Reporting: Social and Environmental Disclosure to Investors in the Chemicals and Banking and Insurance Industry. (7th November 2013) - Lock, Irina; Seele, Peter
Abstract: This paper aims to deepen the understanding of corporate social responsibility (CSR) reporting practices toward stakeholder group investors. Quantitative content analysis was applied to 437 articles of CSR reports from the chemicals, and banking and insurance industries in Germany and Switzerland. The results were benchmarked to the Sarasin sustainability rating's weighting of social and environmental industry risks. It was found that the chemicals industry's CSR reports meet the benchmark, whereas those from the banking and insurance industry do not (RQ1). Swiss chemicals producers perform well in reporting on their specific industry risks, while German companies mirror the sector‐specific risks in the banking and insurance industry (RQ2). The results thus indicate the appropriateness of investor‐specific reporting and suggest – in line with GRI and the European Union – further standardization in order to level the playing field of CSR in Europe. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment